RIPK1 is dispensable for cell death regulation in β-cells during hyperglycemia - Önay Veli; Öykü Kaya; Ana Beatriz Varanda; Ximena Hildebrandt; Peng Xiao; Yann Estornes; Matea Poggenberg; Yuan Wang; Manolis Pasparakis; Mathieu J.M. Bertrand; Henning Walczak; Alessandro Annibaldi; et al. (Elsevier, 2024)
Objective: Receptor-interacting protein kinase 1 (RIPK1) orchestrates the decision between cell survival and cell death in response to tumor necrosis factor (TNF) and other cytokines. Whereas the scaffolding function of RIPK1 is crucial to prevent TNF-induced apoptosis and necroptosis, its kinase activity is required for necroptosis and partially for apoptosis. Although TNF is a proinflammatory cytokine associated with β-cell loss in diabetes, the mechanism by which TNF induces β-cell demise remains unclear. Methods: Here, we dissected the contribution of RIPK1 scaffold versus kinase functions to β-cell death regulation using mice lacking RIPK1 specifically in β-cells (Ripk1β-KO mice) or expressing a kinase-dead version of RIPK1 (Ripk1D138N mice), respectively. These mice were challenged with streptozotocin, a model of autoimmune diabetes. Moreover, Ripk1β-KO mice were further challenged with a high-fat diet to induce hyperglycemia. For mechanistic studies, pancreatic islets were subjected to various killing and sensitising agents. Results: Inhibition of RIPK1 kinase activity (Ripk1D138N mice) did not affect the onset and progression of hyperglycemia in a type 1 diabetes model. Moreover, the absence of RIPK1 expression in β-cells did not affect normoglycemia under basal conditions or hyperglycemia under diabetic challenges. Ex vivo, primary pancreatic islets are not sensitised to TNF-induced apoptosis and necroptosis in the absence of RIPK1. Intriguingly, we found that pancreatic islets display high levels of the antiapoptotic cellular FLICE-inhibitory protein (cFLIP) and low levels of apoptosis (Caspase-8) and necroptosis (RIPK3) components. Cycloheximide treatment, which led to a reduction in cFLIP levels, rendered primary islets sensitive to TNF-induced cell death which was fully blocked by caspase inhibition. Conclusions: Unlike in many other cell types (e.g., epithelial, and immune), RIPK1 is not required for cell death regulation in β-cells under physiological conditions or diabetic challenges. Moreover, in vivo and in vitro evidence suggest that pancreatic β-cells do not undergo necroptosis but mainly caspase-dependent death in response to TNF. Last, our results show that β-cells have a distinct mode of regulation of TNF-cytotoxicity that is independent of RIPK1 and that may be highly dependent on cFLIP.